Civil society in authoritarian regimes: why are some civil society organisations more successful than others? - Sun, Wenzhen (Nanyang Technological University, 2024)
Contrary to the belief that civil societies are to be independent of the state, some Civil Society Organisations (CSO) have demonstrated their ability to coexist with the pervasive authoritarian regimes. This paper will analyse the civil societies in China and Vietnam to uncover how these CSOs function effectively despite the tight authoritarian control. The paper will first discuss the pivotal role of having a cooperative approach where CSOs operates within the boundaries set by the state to avoid state repression. Then, the ‘contingent symbiosis’ narrative will be used to explain the mutually beneficial partnership between CSOs and local governments, which enhances the legitimacy and credibility of CSOs and provides access to crucial resources. While concerns about autonomy persist, the paper contends that flexibility in navigating political contexts by taking advantage of fragmentation and censorship of society can effectively address this issue and allow CSOs to successfully navigate the complex political landscapes in authoritarian states. Through a study of secondary research and qualitative interviews, this paper contributes by providing a more holistic analysis of the factors influencing the success of CSOs in authoritarian states.